On the minimum and maximum operator corresponding to the general elliptical problem with inhomogeneous boundary value conditions - Вarkovsky, V. V.; Roitberg, Y. A.; Барковский, В. В.; Ройтберг, Я. А. (Institute of Mathematics, NAS of Ukraine, 1966)
-